Real-Time Hand Gesture Recognition for Improved Communication with Deaf and Hard of Hearing Individuals - Lakshmi, K.; Samiya; Lakshmi, M. Sri; Kumar, M. Rudra; Singuluri, Prem Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
People who lack knowledge in sign language often face difficulty communicating effectively with those who are deaf or hard of hearing, but in such cases hand gesture recognition technology can provide an easy-to-use alternative for computer communication. This research concentrates on developing a hand gesture recognition system that works in real-time and utilizes universal physical traits present in all human hands as its basis for identifying these movements by automating the identification of sign gestures obtained through webcam footage using Convolutional Neural Networks (CNN) alongside additional algorithms integrated into this framework. Natural hand gestures are used for communication while the system prioritizes segmentation of these movements, and the automated recognition feature of the system is highly beneficial for people with hearing disabilities as it can help eliminate long-lasting communication barriers. The system also has potential applications in areas like human-machine interfaces and immersive gaming technology, so all parties involved can benefit from the ease that real-time hand gesture recognition brings through its potential as a tool for improving communication and reducing barriers faced by those who are deaf or hard of hearing.